Land use Change In Khageri Watershed, Chitwan - Dhakal, Keshav Raj (The Third Pole: Journal of Geography Education, 2014)
This paper is an attempt to analyze land use pattern and its changes between 1978/79 and 1999 in Khageri watershed located in Central Development Region, Nepal. This watershed has mainly been covered with forest followed by agricultural land. The proportion of other land use categories like grazing land, sandy area, and barren land and water bodies is limited. The pattern of land use has been changing in this area. Resettlement program after eradication of malaria and migration of population from other parts of the country are the main causes of this change. The resettlement in the watershed of population from Padampur VDC further accelerated the change. The most remarkable change was from forest to agricultural land. The sandy area has also been increased due to lateral cutting and floods of the Khageri River and deforestation. DOI: http://dx.doi.org/10.3126/ttp.v8i0.11512 The Third Pole: Journal of Geography Vol.8-10, pp. 51-56: 2010